Perbandingan Metode Protective Angle Dan Metode Rolling Sphere Pada Proteksi Tegangan Lebih Saluran Distribusi 13,8 KV PT. Chevron Pacivic Indonesia - Fadil Pradipta; Dian Yayan Sukma; Edy Ervianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
South Bekasap Area PT. Chevron Pacivic Indonesia was an area that has flash density reach at 1,970 flash/km2/year with IKL level at 136 thunder days per year. The amount of lightning current that strikes phase wires can be minimized by using a ground wire. this is done by adjusting the angle between the ground wire to phase wire to form a region that free from lightning strikes called protected region. In the analysis of protected region, first we must determined the level of lightning protective system needs base on standart that used in Indonesia, called SNI-03-7015-2004. From the analysis of hazard assesment, it was found the level of lightning protection needs at level I with striking distance at 20 meter. Based on data and analysis, then it is known that the distribution line 13,8 kV So.Bekasap has level protection system that is less good. In protective angle method calculations, the single poles (type A, B, and C) have protection region at 33o and double poles (type SAA, SBB, and SCC) at 26o. While based on rolling sphere method, the single poles (type A, B, and C) have protection region at 13o and double poles with double ground wires (type SAA, SBB, and SCC) at 27o.Keywords: protected region, protection system, protective angle method, rolling sphere method.